Biomass gasification integrated with CO2 capture processes for high-purity hydrogen production: Process performance and energy analysis. (1st September 2018) - Detchusananard, Thanaphorn; Im-orb, Karittha; Ponpesh, Pimporn; Arpornwichanop, Amornchai
Highlights: An integrated biomass gasification and CO2 capture process is proposed. The utilization of captured CO2 as a gasifying agent is investigated. Energy and exergy analyses of the integrated process are performed. The CaO/C ratio has to be maintained at 3.17 to completely CO2 capture. The energy and exergy efficiencies of the process increase as CO2 /C ratio increases. Abstract: The performance of an integrated biomass gasification and CO2 capture process to produce H2 -rich gas satisfying a PEMFC specification is investigated. Wood residue and CaO are used as a biomass feedstock and a CO2 sorbent, respectively. Modeling of such an integrated process is performed by using ASPEN Plus. The effect of change in major parameters, i.e., gasifying temperature, carbonation temperature and CaO/C ratio, on the product gas composition is investigated. The H2 concentration of the product gas leaving the gasifier is found to increase as the gasifying temperature increases and reaches its maximum value when the gasifying temperature is higher than 700 °C. For the integrated process, the H2 concentration significantly decreases as the carbonation temperature increases to higher than 500 °C. Moreover, the result indicates that the CaO/C ratio should be maintained at a value higher than 3.17 to ensure that the generated CO2 is completely captured. The energetic and exergetic performances, as well as the environmental impact of the integrated process at various amounts of recycled CO2, are also investigated. The energy conversion efficiency and the exergy efficiency based on H2 production increase as the CO2 /C ratio increases, whereas the CO2 emission shows the opposite trend. The maximum exergy efficiency of 69.65%, based on the hydrogen production and the heat generation, is achieved at CO2 /C and CaO/C ratios of 0.6 and 4.48, respectively. At this condition, a specific emission of CO2 of 4.4 g C O 2 - eq M J - 1 and an energy conversion efficiency of 88.09% are achieved.